Endothelial overexpression of endothelin-1 modulates aortic, carotid, iliac and renal arterial responses in obese mice - BARETELLA Oliver; CHUNG Sookja K; XU Aimin; VANHOUTTE Paul M (Acta Pharmacologica Sinica; Vol 38, No 4 (April 2017): Acta Pharmacologica Sinica, 2017)
Endothelin-1 (ET-1) is essential for mammalian development and life, but it has also been implicated in increased cardiovascular risk under pathophysiological conditions. The aim of this study was to determine the impact of endothelial overexpression of the preproendothelin- 1 gene on endothelium-dependent and endothelium-independent responses in the conduit and renal arteries of lean and obese mice. Obesity was induced by high-fat-diet (HFD) consumption in mice with Tie-1 promoter-driven, endothelium-specific overexpression of the prepro-endothelin-1 gene (TEThet) and in wild-type (WT) littermates on a C57BL/6N background. Isometric tension was measured in rings (with endothelium) of the aorta (A), carotid (CA) and iliac (IA) arteries as well as the main (MRA) and segmental renal (SRA) arteries; all experiments were conducted in the absence or presence of L-NAME and/or the COX inhibitor meclofenamate. The release of prostacyclin and thromboxane A2 was measured by ELISA. In the MRA, TEThet per se increased contractions to endothelin-1, but the response was decreased in SRA in response to serotonin; there were also improved relaxations to acetylcholine but not insulin in the SRA in the presence of L-NAME. HFD per se augmented the contractions to endothelin-1 (MRA) and to the thromboxane prostanoid (TP) receptor agonist U46619 (CA, MRA) as well as facilitated relaxations to isoproterenol (A). The combination of HFD and TEThet overexpression increased the contractions of MRA and SRA to vasoconstrictors but not in the presence of meclofenamate; this combination also augmented further relaxations to isoproterenol in the A. Contractions to endothelin-1 in the IA were prevented by endothelin-A receptor antagonist BQ-123 but only attenuated in obese mice by BQ-788. The COX-1 inhibitor FR122047 abolished the contractions of CA to acetylcholine. The release of prostacyclin during the latter condition was augmented in samples from obese TEThet mice and abolished by FR122047. These findings suggest that endothelial TEThet overexpression in lean animals has minimal effects on vascular responsiveness. However, if comorbid with obesity, endothelin-1-modulated, prostanoidmediated renal arterial dysfunction becomes apparent.